Highest ambulatory speed using Lokomat gait training for individuals with a motor-complete spinal cord injury: a clinical pilot study - van Silfhout, Lysanne; Váňa, Zdenĕk; Pĕtioký, Jakub; Edwards, Michael J R; Bartels, Ronald H M A; van de Meent, Henk; Hosman, Allard J F (Acta neurochirurgica, 2020)
BACKGROUND: Motor impairment and loss of ambulatory function are major consequences of a spinal cord injury (SCI). Exoskeletons are robotic devices that allow SCI patients with limited ambulatory function to walk. The mean walking speed of SCI patients using an exoskeleton is low: 0.26 m/s. Moreover, literature shows that a minimum speed of 0.59 m/s is required to replace wheelchairs in the community. OBJECTIVE: To investigate the highest ambulatory speed for SCI patients in a Lokomat. METHODS: This clinical pilot study took place in the Rehabilitation Center Kladruby, in Kladruby (Czech Republic). Six persons with motor-complete sub-acute SCI were recruited. Measurements were taken at baseline and directly after a 30 min Lokomat training. The highest achieved walking speed, vital parameters (respiratory frequency, heart rate, and blood pressure), visual analog scale for pain, and modified Ashworth scale for spasticity were recorded for each person. RESULTS: The highest reached walking speed in the Lokomat was on average 0.63 m/s (SD 0.03 m/s). No negative effects on the vital parameters, pain, or spasticity were observed. A significant decrease in pain after the Lokomat training was observed: 95% CI [0.336, 1.664] (p = 0.012). CONCLUSION: This study shows that it is possible for motor-complete SCI individuals to ambulate faster on a Lokomat (on average 0.63 m/s) than what is currently possible with over-ground exoskeletons. No negative effects were observed while ambulating on a Lokomat. Further research investigating walking speed in exoskeletons after SCI is recommended.
Keywords: Robotics; exoskeleton; Humans; lidé středního věku; poranění míchy; Female; Exercise Therapy; dospělí; Spinal Cord Injuries; rychlost chůze; lidé; pilotní projekty; Pilot Projects; Walking Speed; Adult; ženské pohlaví; Male; Muscle Spasticity; Middle Aged; Exoskeleton Device; svalová spasticita; mužské pohlaví; terapie cvičením; robotika